Pharmacokinetics and Pharmacodynamics of diclofenac in the presence and absence of glibenclamide in the rat - María R León-Reyes; Gilberto Castañeda-Hernández; Mario I Ortiz (Frontiers Media S.A., 2016)
PURPOSE. There are evidences that glibenclamide, a sulfonylurea antidiabetic agent, reduces the analgesic action of non-steroidal anti-inflammatory drugs (NSAIDs), opioids and neuromodulators in animal models. The purpose of this work was to examine in the rat if such interaction involves pharmacokinetic mechanisms or is solely limited to the pharmacodynamic level. METHODS. All studies were carried out in female Wistar rats. Analgesia was assessed using the formalin test. Fifty microliters of diluted formalin was injected subcutaneously into the dorsal surface of the right hind paw. Nociceptive behavior was quantified as the number of flinches of the injected paw during 60 min after injection and a reduction in formalin-induced flinching was interpreted as an analgesic response. Rats were treated with oral diclofenac (3-18 mg/kg) in presence and the absence of oral glibenclamide (1-30 mg/kg). To evaluate the possibility of a pharmacokinetic interaction, the oral bioavailability of diclofenac (18 mg/kg) was studied in presence and the absence of glibenclamide (10 mg/kg). RESULTS. Oral administration of diclofenac produced a dose-dependent antinociceptive effect in the formalin test. Coadministration of glibenclamide significantly reduced diclofenac-induced antinociception. Notwithstanding, the interaction does no appear to involve pharmacokinetic mechanisms, as oral glibenclamide failed to produce any significant alteration in oral diclofenac bioavailability. CONCLUSION. Concomitant systemic administration of glibenclamide and diclofenac results in a reduction of the analgesic effect of the NSAID in the formalin test in the rat. This interaction, however, appears due solely to a pharmacodynamic mechanisms as diclofenac pharmacokinetics are not altered.